Strategi Guru Baca Tulis Al-Qur’an (BTQ) Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa Kelas 2 Madrasah Ibtida’iyah Mamba’ul Hikmah Kerten Teguhan Paron Ngawi Tahun Ajaran 2024/2025 - Binti Solikah; Joko Purnomo; Febrianingsih, Dian (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The Qur'an is a holy book that is believed to be true by Muslims, and guaranteed its purity and authenticity by Allah SWT. Therefore, there is no doubt as to its contents. The first step in such an introduction is the ability to read it well. Referring to the first revelation revealed to the Prophet Muhammad SAW, it is implied that the command to read contains the meaning that through reading activities, humans can obtain knowledge and are encouraged to continue to seek and explore knowledge, especially from the Qur'an. This study aims to examine the strategies of Qur'an literacy teachers (BTQ) at MI Mamba'ul Hikmah in improving the Qur'an reading ability of grade 2 students. This research uses a qualitative descriptive approach with data sources obtained from interviews, observations and documentation activities and then supported by several literacy related to the research theme. The results of the study show that the strategies applied by BTQ teachers are in 3 ways, namely the application of the lecture method, the practice method and the question and answer method, of the three strategies are then implemented in 2 ways, namely by grouping students based on the ability to read the Qur'an and also by habitual activities of reading the Qur'an in congregation. The supporting factors for BTQ teachers include the existence of guidebooks and also parental support. The inhibiting factors are the limited teaching time and also the lack of facilities and infrastructure to support learning.